The room where it happened : a White House memoir - Bolton, John 1948- (Simon & Schuster, 2020)
"John Bolton served as National Security Advisor to President Donald Trump for 519 days. A seasoned public servant who had previously worked for Presidents Reagan, Bush #41, and Bush #43, Bolton brought to the administration thirty years of experience in international issues and a reputation for tough, blunt talk. In his memoir, he offers a substantive and factual account of his time in the room where it happened." --